2019
DOI: 10.15619/nzjp/47.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of cardiopulmonary resuscitation amongst New Zealand physiotherapists

Abstract: Cardiopulmonary resuscitation (CPR) is an essential life-saving skill shown to save lives and improve outcomes of survivors. Physiotherapists are ethically obliged to ensure the safety of patients and to assist in an emergency if required. The purpose of this study was to explore the knowledge and perceptions of CPR amongst New Zealand physiotherapists. Chi-square statistics were used to test associations between the independent variables of age, sex, years of experience, scope and place of work, and postgradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 10 publications
5
8
0
1
Order By: Relevance
“…Hence, it is crucial to know the location of the nearest accessible AED and how to use it correctly. Harvey et al (2019) found physiotherapists older than 39 years of age were more likely to be incorrect to specific AED knowledge questions than younger physiotherapists. Modern technology has made locating AEDs easier with mobile phone applications that can put this information in the palm of your hand.…”
Section: Cpr Is Only Part Of the Picture: Where Is The Nearest Defibrmentioning
confidence: 81%
See 4 more Smart Citations
“…Hence, it is crucial to know the location of the nearest accessible AED and how to use it correctly. Harvey et al (2019) found physiotherapists older than 39 years of age were more likely to be incorrect to specific AED knowledge questions than younger physiotherapists. Modern technology has made locating AEDs easier with mobile phone applications that can put this information in the palm of your hand.…”
Section: Cpr Is Only Part Of the Picture: Where Is The Nearest Defibrmentioning
confidence: 81%
“…The framework states that "sports physiotherapists must hold up-to-date competencies in basic life support and management of acute trauma situations" (Physiotherapy Board of New Zealand, 2018, p. 80). Surprisingly, the recent survey of New Zealand physiotherapists found that clinicians working in private practice, public hospitals and community settings were more likely to have CPR certification compared to those working with sports teams (Harvey et al, 2019). Harvey et al (2019) reported that about half (56%) of respondents had completed formal CPR training in the 12 months before participating in the survey.…”
Section: Patient Safetymentioning
confidence: 97%
See 3 more Smart Citations